Comparative Cost Analysis of Hypercholesterolemia Treatment: Allopathic Medicine and Ayurveda Medicine (International Journal of Ayurveda and Pharma Research, 2024)
The cost of treatment is very high for CVD and the prevalence of hypercholesterolemia is also very high in developing countries. Many Indian people do not have basic amenities and medical facilities are also not accessible. So alternative medicine can play an important role in the treatment of high cholesterol. Arjuna and Kutki are effective medicines in treating high cholesterol. Methodology: Comparative cross sectional study was planned to determine the socio-economic, and demographic status and comparison of treatment costs of high cholesterol patients in SS Hospital, IMS, BHU, Varanasi. Result: The overall expenditure for Group B is significantly high (3670.06) compared to Group A (1341.10). Medicine costs form the largest portion of expenses in Group B (1:4.8), while laboratory costs are the largest in Group A. Discussion: The economic burden poses a significant challenge in the treatment of any illness. Elevated cholesterol levels pose a significant problem in the current state of affairs in India. Developing countries face significant challenges in managing their financial issues.